Researching L2 writers' use of metadiscourse markers at intermediate and advanced levels. (July 2019) - Bax, Stephen; Nakatsuhara, Fumiyo; Waller, Daniel
Abstract: Metadiscourse markers refer to aspects of text organisation or indicate a writer's stance towards the text's content or towards the reader (Hyland, 2004:109). The CEFR (Council of Europe, 2001) indicates that one of the key areas of development anticipated between levels B2 and C1 is an increasing variety of discourse markers and growing acknowledgement of the intended audience by learners. This study represents the first large-scale project of the metadiscourse of general second language learner writing, through the analysis of 281 metadiscourse markers in 13 categories, from 900 exam scripts at CEFR B2-C2 levels. The study employed the online text analysis tool Text Inspector (Bax, 2012), in conjunction with human analysts. The findings revealed that higher level writers used fewer metadiscourse markers than lower level writers, but used a significantly wider range of 8 of the 13 classes of markers. The study also demonstrated the crucial importance of analysing not only the behaviour of whole classes of metadiscourse items but also the individual items themselves. The findings are of potential interest to those involved in the development of assessment scales at different levels of the CEFR, or to teachers interested in aiding the development of learners. Highlights: Advanced L2 writers use fewer metadiscourse markers than intermediate writers. Advanced L2 writers can express text organisation without explicit markers. Higher-level writers use a greater range of metadiscourse markers. Higher-level writers abandon simple markers in favour of other makers.